2014
DOI: 10.4081/jphr.2014.208
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Perceptions of Neighbourhoodresources, Sense of Coherence and Health for Different Groups in a Norwegian Neighbourhood

Abstract: BackgroundHealth and conditions for health are unevenly distributed across neighbourhoods. Within a salutogenic perspective, neighbourhood-resources can be internalised, and become generalised resistance resources. This paper aims to examine whether the neighbourhood could be a supportive arena for health-promotion, and for whom.Design and MethodsA cross-sectional study, based on register data from the population-survey in Malvik, Norway, (N=865) was conducted. Using multiple regression analysis, total sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 32 publications
1
34
0
1
Order By: Relevance
“…Relating to this "how" question, we review some studies which have already attempted to do so. Our interdisciplinary review starts with some studies which found positive interactions between SOC and the relations between members of the same community (e.g., Maass, Lindström, & Lillefjell, 2014;. Indeed, this evidence can be explained by the well-known relationship between strong social connection or connectivity and enhanced sense of health and well-being (Vaandrager & Kennedy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Relating to this "how" question, we review some studies which have already attempted to do so. Our interdisciplinary review starts with some studies which found positive interactions between SOC and the relations between members of the same community (e.g., Maass, Lindström, & Lillefjell, 2014;. Indeed, this evidence can be explained by the well-known relationship between strong social connection or connectivity and enhanced sense of health and well-being (Vaandrager & Kennedy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Relating to this "how" question, we review some studies which have already attempted to do so. Our interdisciplinary review starts with some studies which found positive interactions between SOC and the relations between members of the same community (e.g., Maass, Lindström, & Lillefjell, 2014;Morton & Lurie, 2013;Teig et al, 2009). Indeed, this evidence can be explained by the well-known relationship between strong social connection or connectivity and enhanced sense of health and well-being (Vaandrager & Kennedy, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For older adults, proximate locations and accessibility to key resources were linked to social participation (Richard et al, 2013). The relative importance of the residential area and its resources differs across groups, and might partly be dependent on having access to other important societal arenas, like the workplace (Maass et al, 2014). Additionally, different factors promote heath in healthy and in less healthy people (Fuller, Stewart Williams, & Byles, 2010).…”
Section: The Healthy City Networkmentioning
confidence: 99%
“…There are few studies examining the links between city resources, sense of coherence, and health outcomes. Emerging evidence suggests that the development of a strong sense of coherence might be dependent on processes linked to planning, establishment, and maintenance, as well as perceived quality of resources (Bull et al, 2013;Maass et al, 2014). This is linked to the context-dependence of resources.…”
Section: Links Between Environmental Resources Place and Salutogenesismentioning
confidence: 99%